Clinical Manual of Total Cardiovascular Risk - Poulter, Neil R. (Springer London : Imprint: Springer, 2009)
Cardiovascular disease (CVD) is a major cause of morbidity and mortality in Western industrialized countries. The management of non-fatal stroke and heart attack consumes a major proportion of current healthcare budgets and has a huge detrimental impact on quality of life for both patients and their relatives. The multifactorial nature of CVD and the interactions between risk factors mean that it is difficult for clinicians to make an intuitive assessment of an individual's future risk of disease. This has led to the production of a number of guidelines on the prevention of CVD, all of which recommend risk assessment tools to guide primary prevention strategies. In a practical, easy to digest format, Clinical Management of Total Cardiovascular Risk presents the key data on all aspects of managing cardiovascular disease. Stressing the importance of identifying the patient at risk, Neil Poulter incorporates review of the current guidelines and outlines the options available when diagnosing, managing and treating these patients. Using algorithms to highlight key management decisions, this practical reference will be useful to all in the management of cardiovascular disease from primary care practitioners and physicians in the fields of prevention and rehabilitation to Residents in Internal Medicine and Cardiology.